NCMP-19. SIDE EFFECTS FROM CHEMOTHERAPY VERSUS SYMPTOMS FROM COVID-19 INFECTION - Du, Senxi (Neuro Oncol, 2020)
INTRODUCTION: Adverse effects from chemotherapy such as high dose methotrexate (HD-MTX) are seen during and after chemotherapy. During this coronavirus disease 2019 (COVID-19) pandemic period, COVID-19 infection symptoms following chemotherapy due to immune compromise could mimic chemotherapy associated side effects. Differentiation on time is needed for correct management. CASE REPORT: A 50-year old male with clinical history of ocular lymphoma underwent HD-MTX therapy. Before admission, his routine COVID-19 test was negative. After receiving HD-MTX, he developed fatigue, nausea and vomiting. The symptoms resolved before discharge. Next day after discharge, he developed diarrhea, fatigue, subjective fever and feeling cold. His temperature was normal. His symptoms have been persistent for 4-5 days and have resolved gradually and spontaneously. Family members have had no symptoms. The patient denies COVID-19 contact history. The above symptoms were considered adverse effects from chemotherapy. The patient did not seek medical attention. Prior to admission for next cycle of HD-MTX, COVID-19 test was found positive. Chemotherapy was on hold. The patient started home quarantine. The patient has been doing well and practiced COVID-19 infection precaution at home. DISCUSSION: The fatigue, nausea and vomiting during HD-MTX treatment are adverse effects from chemotherapy while the diarrhea, fatigue, subjective fever and chills developed after discharge are symptoms of COVID-19 infection. Our case highlights the importance of keeping in mind and differentiating between side effects from chemotherapy and symptoms of COVID-19 viral infection in cancer patients who receive chemotherapy.